Algorithmic leadership and algorithmic management : a systematic literature review - Feshchenko, Polina (2021)
Digitalization and automation technologies are transforming our lives, work dynamics and organizations. They give birth and enable totally new forms of organizational design – labor platforms, such as Uber, Wolt, Upwork and many other, - represent a new phenomenon, with a new managerial practice, in which the role of a human manager is diminished or non-existent. Over and above, both industry and research talk about potential of Artificial Intelligence to be part of the corporate board of organizations or even fully leading the course of their action. Some of these technology applications, like algorithmic leadership, are still yet to come, with many things to weight and consider before their implementation. At the same time, some have already been here as a real practice - algorithmic management – a system that is able to coordinate, monitor and organize workforce on its own, without human intervention. Due to these contemporary practices being topical at the moment and also, generally, fascinating to explore, this systematic review summarises the evidence of the present research done within the field. Its findings bring value for the advancement of research and for the industrial implementations of automation technologies for mediating management of the workforce. Among the main discoveries was the lack of communication in the work arrangement under algorithmic management, between all the parties involved – workers, organization and the system. A significant number of researchers in the field highlights the importance of social media usage, while some suggest that there is still a place, yet a different one, for human managers within these modern working structures.